Predators of Gonipterus platensis (Marelli, 1926) (Coleoptera: Curculionidae) larvae in Antioquia, Colombia (2019)
The eucalyptus snout beetle, Gonipterus spp. are a pest of eucalyptus worldwide (Figure 1). Gonipterus platensis was rst reported in Colombia in 2016, threatening and causing economic losses in more than 60.000 ha of Eucalyptus spp. planted in the country. Classical biological control of these species has been e ective in some countries with Anaphes nitens (Girault) and A. inexpectatus Huber & Prinsloo, 1990 (Hymenoptera: Mymaridae), and complemented with di erent natural enemies (NE) (Nascimento et al. 2017).